(untitled) (Bangladesh Journal of Medical Education, 2014)
Objectives To assess the level of job satisfaction among the medical teachers according to their views including existing barriers and ways of further improvement. Materials and methods This was a cross sectional type of descriptive study and was carried out for one year. In depth interview were performed using interview schedule among twenty five medical teachers those were willing to participate in this study and working in preclinical, Para clinical and clinical departments of 5 non government and 5 government medical colleges. Results: In depth interview was conducted among 11 assistant professors, 6 associate and 8 professors . Among them 12 teachers were working in non government and 13 in government medical colleges. Of them 3 teachers were from preclinical ,5 from paraclinical and 17 from clinical departments. Expressed satisfaction level was very low in 5 (20%), low 12 (48%), moderate 5(20%), high 2(8%) and undecided1(4%) .Good academic environment ,good relation with administration, colleagues and students, job security and location of the institute causes much satisfaction. Main causes of dissatisfaction includes political interference in posting, transfer and promotion of the medical teachers. Low salary, lack of necessary teaching materials. Fifty percent teachers had expressed their dissatisfaction regarding their working place. All of the teachers believed that job satisfaction influences teaching quality and there should be provision for professional development of teachers. Conclusion Job satisfaction among medical teachers is low. There are several causes of satisfaction and so many causes of dissatisfaction. Political consideration in cases of recruitment, posting, transfer and promotion , low salary ,lack of educational materials and educational environment is very important issue for causing dissatisfaction. On job training for professional development of teachers is recommended by all. DOI: http://dx.doi.org/10.3329/bjme.v2i2.18137 Bangladesh Journal of Medical Education Vol.2(2) 2011: 18-25